Risk Factors of Fungal Growth in Sputum Culture from Severe and Critical COVID-19 Patients - Theresia Novi; B. Rina Aninda Sidharta; Heru Wijono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Patients infected with Coronavirus Disease (COVID-19), especially those with comorbidities, immunosuppressive treatment, intubated, and on ventilators, are more likely to contract fungal infection. This study aimed to describe the profile of fungal growth in sputum culture from severe and critical COVID-19 patients, and to determine the association between the fungal growth with the patient's outcome and the association between several risk factors with the fungal growth. A retrospective case-control study was carried out at Husada Utama Hospital, Surabaya. This study samples were 119 patients; fungal growth on sputum culture was seen in 64 (53.8%) patients; the three types of fungi with the highest frequency were Cryptococcus neoformans found in 23 (19.3%) patients, Candida tropicalis found in 11 (9.2%) patients and Candida dubliniensis found in 10 (8.4%) patients. There was no significant association between fungal growth and patient mortality with a p-value of 0.940 (p>0.05), also between the patient's history of diabetes mellitus and fungal growth (p=0.496) and between corticosteroid treatment and fungal growth (p=0.168). Still, there was a significant association between the use of ventilators in patients and fungal growth with a p-value of 0.001 (p<0.05). A significant association was also found between IL-6 inhibitor (Tocilizumab) treatment and fungal growth with a p-value of 0.003 (p<0.05). The most common fungi found in this study with the highest frequency was Cryptococcus neoformans. There was an association between two risk factors (the use of a ventilator and tocilizumab treatment) and fungal growth.